PHYLOGENETIC AND IDENTIFICATION OF PHITSANULOK’S LANDRACE RICE BASED ON NUCLEOTIDE SEQUENCE ANALYSIS OF TRNH-PSBA - Jongjitvimol, Touchkanin; Urtgam, Sittichai (Life Sciences and Environment Journal, 2020)
Landrace rice identification is generally based on morphological characters, which is costly, labor-intensive including time-consuming process. This study was aimed to improve the identification of Phitsanulok’s Landrace rice assay using DNA barcoding based on nucleotide sequence diversity at trnH-psbA locus. The PCR product was amplified corresponding to 650 bp long which could classify Phitsanulok’s landrace rice into 2 groups. Ton Dip and Lao is the farthest evolution from the ancestor. Individual sequence among 35 landrace-rice cultivars had a high genetic divergence (%K2P) approximately 19%, compared to Oryza sativa L. and 1.3% within group of the Phitsanulok’s landrace rice. Thirty out of Phitsanulok’s landrace rice cultivated varieties was able to be identified by using DNA barcode at trnH-psbA locus with the high efficient of 85.71%. This finding is the first report of implemented DNA barcode at trnH-psbA locus to identify Thai landrace rice’s subspecies using trnH-psbA DNA barcode . However, the combinations of more two DNA barcodes with different loci would be further experimental for increasing efficiency of identification in landrace rice cultivated varieties.